THEORETICAL FRAMEWORK OF CORPORATE GOVERNANCE PRINCIPLES (Scientific Journal of Actuarial Finance and Accounting, 2024)
The complex concept of corporate governance includes several interrelated aspects: regulatory, legal, organizational, cultural, ethical and informational. Today, in modern corporate practice, a high level of development of corporate governance is one of the factors in increasing the investment attractiveness of companies. The level of quality of corporate governance affects decision-making on the possibility of investing in a company and affects its capitalization. The introduction of effective mechanisms and principles of corporate governance helps to increase the value of the company and the implementation of intra-company interests in the emerging national model of corporate governance.